The Indonesian species of Macrophthalmus Desmarest, 1823, with the description of a new species (Crustacea: Decapoda: Brachyura: Macrophthalmidae) - Rahayu, Dwi Listyo; Nugroho, Dharma Arif (Zootaxa, 2012)
Fourteen species of Macrophthalmus Desmarest, 1823, are reported from Indonesia, of which two species, Macrophthal-mus (Macrophthalmus) abbreviatus Manning & Holthuis, 1981, and M. (Macrophthalmus) sulcatus malaccensis Tweedie,1937, are recorded for the first time from the region, and one new species M. (Mareotis) fusculatus n. sp. is described. Thenew species resembles M. (Mareotis) definitus Adams & White, 1849, in the relatively narrow male abdomen and mod-erately long, curved tip of the male G1. However, the differences are noticeable in the morphology of the carapace of thenew species which is divergent posterolateraly, the presence of tubercles on the gastric, cardiac and intestinal regions, and the absence of a longitudinal row of granules or setae on the branchial region.